Pengaruh Motif Khulu’ Terhadap ’Iwadh Perspektif Kompilasi Hukum Islam (KHI) dan Fikih Madzhab - Aminudin, Sugeng (STAINI Press, 2024)
This study discusses the influence of the khulu' motif on 'Iwadh in the perspective of the Compilation of Islamic Law (KHI) and madzhab fiqh. This study uses a literature method with a descriptive-historical approach, this study makes a comparison between the two perspectives. The findings show that the KHI does not distinguish between ordinary divorce and khulu' as applicable in Islamic law. KHI only regulates the khulu' ordinance without considering motives as the basis for determining 'Iwadh. On the other hand, madzhab fiqh expressly links the khulu' motive with ransom, such as khulu' without cause, because of the husband's tyranny, or because the husband troubles his wife. This affects the validity or not of khulu' and the halal or haram of 'Iwadh. From a legal point of view, Article 124 of the KHI states that khulu' must be based on the grounds of divorce according to Article 116, which can cause injustice to the wife if she still has to pay 'Iwadh to the husband who wronged her. In addition, Article 148 paragraph 6 of the KHI allows religious courts to decide the amount of the ransom if there is no agreement between the husband and wife, which can lead to injustice, especially if the husband is innocent.